Hydrogen peroxide-induced apoptosis is CD95-independent, requires the release of mitochondria-derived reactive oxygen species and the activation of NF-κB - Dumont, Andreas; Hofmann, Thomas G.; Dröge, Wulf (Oncogene, 1999)
Reactive oxygen species (ROS) play an important role in cell death induced by many different stimuli. This study shows that hydrogen peroxide-induced apoptosis in T-cells did not require tyrosine kinase p56lck, phosphatase CD45, the CD95 receptor and its associated Caspase-8. H2O2-triggered cell death led to the induced cleavage and activation of Caspase-3. Hydrogen peroxide-treatment of T-cells resulted in the formation of mitochondrial permeability transition pores, a rapid decrease of the mitochondrial transmembrane potential ΔΨm and the release of Cytochrome C. Inhibition of the mitochondrial permeability transition by bongkrekic acid (BA), or interference with the mitochondrial electron transport system by rotenone or menadione prevented the cytotoxic effect of H2O2. Antimycin A, a mitochondrial inhibitor that increases the release of mitochondrial ROS (MiROS), enhanced apoptosis. Overexpression of Bcl-2 and the viral anti-apoptotic proteins BHRF-1 and E1B 19K counteracted H2O2-induced apoptosis. Pharmacological and genetic inhibition of transcription factor NF-κB protected cells from hydrogen peroxide-elicited cell death. This detrimental effect of NF-κB mediating hydrogen peroxide-induced cell death presumably relies on the induced expression of death effector genes such as p53, which was NF-κB-dependently upregulated in the presence of H2O2.
Gesehen am 09.02.2021